PENANAMAN NILAI-NILAI PLURALISME DALAM MITIGASI BENCANA SOSIAL DI DESA SIDADADI, HAURGEULIS, INDRAMAYU - Rahim, Abdur; Mahmudah, Sofia Maqom Al; Riyadi, Sugeng; Nisrina, Risa; Sugino, Sugino; Isu, Mutimah Nursabilah; Sabillah, Miftah; Akmal, Najmuddin; khoirunnisa, Siti; Otistaviany, Heluny (LPPM Universitas Bina Bangsa, 2025)
Diversity in Indonesia can be seen from the many ethnic groups that exist, while social disasters are a very complex phenomenon and have a broad impact on society. Social disaster mitigation is very important to create community resilience. The aim of this Community Service is to instill pluralism values ​​that are relevant to be applied in the context of social disaster mitigation in Sidadadi Village. The results of this Community Service activity show that instilling pluralist values ​​in Sidadadi Village is very important in efforts to mitigate social disasters. In diverse social contexts, the values ​​of pluralism function as a bridge to create harmony between citizens. Data from the Central Statistics Agency shows that Sidadadi Village has significant religious and cultural diversity, with the majority of the population being Muslim. This creates challenges as well as opportunities in handling social disasters. Community Service also found that communities that are more pluralist tend to be more resilient to social disasters, because they have stronger social networks and support each other in crisis situations.